Rigidez de jure y de facto en los términos generales para clases naturales - Miranda, Rafael (2012)
“De jure and De facto Rigidity in the General Terms for Natural Kinds”. This paper will argue that one of rigidity’s central problems in general terms for natural kinds, is consequence of not distinguishing between de jure rigid terms and de facto rigid terms on these cases. The paper claims that necessary identity sentences defended by Kripke in Naming and Necessity consider the term’s occurrence to designate a same kind (kinds which share the transworld relation of being one same kind) through two rigidity terms, a de jure one, and a de facto one. This allows to explain the problems that arise from the notion of rigidity in the case of general terms for natural kinds, since it maintains the causal connection requirements, while at the same time it enunciates the identity criterion between these kinds, through the essential property(ies) of the abovementioned kind.